Use of an aromatase inhibitor in children with congenital adrenal hyperplasia: Impact of anastrozole on bone mineral density and visceral adipose tissue. (15th May 2019) - Halper, Alyssa; Sanchez, Belen; Hodges, James S.; Dengel, Donald R.; Petryk, Anna; Sarafoglou, Kyriakie
Abstract: Objective: Anastrozole, an aromatase inhibitor, has been used off‐label in males with short stature to delay bone maturation. No studies have examined anastrozole's effect on bone mineral density (BMD) or body composition in children with congenital adrenal hyperplasia (CAH) due to 21‐hydroxylase deficiency. Our objective was to evaluate anastrozole's effect on BMD and visceral adipose tissue (VAT) in children with CAH. Design: Total body BMD (TBMD) and L2‐L4 BMD Z ‐scores were adjusted for height‐for‐age Z ‐scores (TBMDHAZ and L2‐L4HAZ ). Hydrocortisone doses (mg/m 2 /d) were averaged over the previous year. Comparison of treated vs not treated with anastrozole used linear regression adjusting for age, pubertal status, sex, CAH type, years on hydrocortisone, BMI Z ‐scores and bone age Z ‐scores. Patients: We compared 25 children with CAH treated with anastrozole (mean age 11.3 [SD 3.0] years, 56% males) vs 31 children with CAH not treated with anastrozole (13.5 [SD 4.6], 29%). Participants underwent a pubertal exam, bone age X‐ray and dual X‐ray absorptiometry (DXA) scan. Results: Average bone age Z ‐score of 4.3 SDs on beginning anastrozole decreased to 1.9 SDs at time of DXA exam ( P = 0.0004) 5.2 (SD 2.2) years later. TBMD Z ‐scores ( P = 0.51), L2‐L4 BMD Z ‐scores ( P = 0.66), VAT ( P = 0.38), TBMDHAZ Z ‐scores ( P = 0.66) and L2‐L4HAZ Z ‐scores ( P = 0.41) did not differ between children treated vs not treated with anastrozole. Conclusion: Anastrozole significantly reduced bone age advancement in children with CAH and advanced bone age (>2SDs) without adverse effects on BMD or VAT. Longitudinal studies of anastrozole in children with CAH are needed to validate these findings.